A cross-sectional study on posttraumatic growth and influencing factors among parents of premature infants - Wang Xingyanan; Lv Yuanhong; Liu Yang; Xiao Zhitian (BMC Pregnancy and Childbirth)
Abstract Objective Preterm birth is a significant public health concern that negatively affects parents’ mental health. Posttraumatic growth (PTG) is a positive response to trauma that can effectively help parents cope with the stress of preterm birth. However, few studies have investigated PTG among parents with preterm infants. This study aimed to examine the level and influencing factors of PTG among parents with preterm infants and to explore its relationship with social support coping styles. Methods A cross-sectional study was conducted among 160 parents of premature infants in a hospital in Shenzhen, China, from May 2022 to August 2022. Parents’ demographic information and birth-related characteristics were collected through a self-designed general information questionnaire. PTG was assessed using the Chinese version of the Posttraumatic Growth Inventory (PTGI). Social support and coping style were measured using the Social Support Scale(SSS) and the Ways of Coping Questionnaire(WCQ). Pearson correlation analysis was used to investigate the relationship between PTGI and WCQ and SSS .A stepwise multiple linear regression analysis was performed to explore independent influencing factors of PTG. Results The parents had an average PTG score of 66.41 ± 10.37, with 81.11% having a low and medium level of PTG. The total score of coping style of parents of premature infants was (34.28 ± 4.97) points, which was in the middle and upper level; the total score of social support of parents of premature infants was (14.28 ± 4.97) points, which was in the middle level. In addition, older gestational age at birth (B = 2.396, P < 0.001) ,higher Apgar score at 5 min at birth (B = 2.117, P = 0.023), positive coping style (B = 0.850, P < 0.001), and higher social support score (B = 1.978, P < 0.001) were associated with higher PTG scores. Conclusion Parents of preterm infants have low to medium levels of PTG, indicating much room for improvement. Older gestational age, higher Apgar score at five minutes at birth, positive coping styles, and high levels of social support were associated with higher PTG levels. Our findings provide helpful guidance for the development of effective and targeted intervention programs to improve parents’ PTG and well-being.